B. 25/20 using gcf simplified is 5/4
Answer:
Step-by-step explanation:
if you see a person that sends you a sketchy link dont click it is an ip grabber.
Answer:
B
Step-by-step explanation:
Answer:
f(x)=x^2+3
f(x+y)=(x+y)^2+3
this is done by replacing x with (x+y)
f(x+y)=x^2+2xy+y^2+3
therefore : f(x+y)= x^2+y^2+2xy+3
So a=2 since a is next to the first 2 it would be 2x2 which equals 4 next it’s B and B= -3 so -3x4 equals -12 and then c also equals 2 so it would be -12x2 and that equals -24. Moving on to the next part as I said a=2 so it would be 3x2 and that equals 6 next it’s B again so 6x -3 equals -18 so now take -24 and -18 and subtract them and you would get -6. Sorry if this answer is wrong I did my best...hope it helped.